Pengembangan Aktivitas Pembelajaran Mengasosiasi Berbasis Media Gambar Berseri Dalam Meningkatkan Proses Kognitif Siswa - Anak Agung Gede Agung; I Wayan Widiana; Ni Kadek Savitri Indrasuari (Universitas Pendidikan Ganesha, 2017)
The purpose of this research is to know the difference of cognitive process between group of students using learning associate activity based on media of serial image in scientific approach and students who learn to use conventional learning activity in fourth grade students even semester of academic year 2016/2017 at elementary school of Sukasada district. This type of research is a quasi experiment with post test only control group design. The population of this study amounted to 255 students. While the sample amounted to 54 students. The data collected in this research is cognitive process test using 19 essay test. The hypothesis was tested using t-test inferential statistics. The results showed that there were significant differences in cognitive processes between groups of students using learning associate activities based on serialized media in scientific approach and students learning using conventional learning activities (tcount = 8,58> ttable = 2,00665).